El proceso de envejecimiento demográfico en Granada y su área metropolitana. The process of demographic aging in Granada and its metropolitan area - Sánchez González, Diego (Universidad de Granada, 2005)
In recent decades, urban residential changes reflect the progression of aging in the Andalucian capital and the expulsion of young people to its metropolitan area. The current context provides a basis to further our understanding of the evolution, structure and spatial distribution of elderly people in the municipalities of the metropolitan area of Granada. The article addresses the difference in the aging specialty in metropolitan context, although special attention to the central city and its social problems. This investigation reveals the existence of significant relationships between the demographic (aging population) and socio-economic and urban dynamics (the problem of housing, equipment and services). En las últimas décadas los cambios residenciales urbanos reflejan el avance del envejecimiento demográfico en las capitales andaluzas y la expulsión de población joven a su Área metropolitana. Este contexto actual sirve de base para ahondar en el conocimiento de la evolución, estructura y distribución espacial del envejecimiento de la población en los municipios del área metropolitana de Granada. En el artículo se aborda la especialidad diferencial del envejecimiento en su contexto metropolitano, aunque prestando especial atención al municipio central y su problemática social. De esta investigación se desprende la existencia de unas relaciones significativas entre la estructura demográfica (envejecimiento poblacional) y la propia dinámica socioeconómica y urbanística (el problema de la vivienda, los equipamientos y servicios).